Measuring and understanding carbon storage in afforested soils by physical fractionation - Paustian, K., author; Paul, Eldor A., author; Gregorich, E. G., author; Morris, S. J., author; De Gryze, S., author; Lenders, S., author; Callewaert, P., author; Six, J., author; Soil Science Society of America, publisher (Colorado State University. Libraries, 2002)
Forested ecosystems have been identified as potential C sinks. However, the accuracy of measurement and understanding of the underlying mechanisms for soil organic C (SOC) storage in forested ecosystems needs to be improved. The objective of this study was to use aggregate and soil organic matter (SOM) fractionation techniques to identify SOC pools that preferentially stabilize SOC in the long term and elucidate SOC sequestration mechanisms in forested soils. At two sites (Wildlife area, Ohio and Kemptville, Ontario) representing two different soils (Hapludalf and Hapludoll), we sampled soils under agriculture, afforestation, and forest and separated them into aggregates. Different size classes of intra-aggregate particulate organic matter (iPOM) fractions were isolated by density flotation, dispersion, and sieving. At both sites, aggregation and whole SOC content were greater in the forested than in the agricultural ecosystems. The greater aggregation in forested ecosystems resulted in greater iPOM C concentrations, especially the iPOM C fractions associated with microaggregates (53–250 μm) and microaggregates occluded within macroaggregates (mM) (250–2000 μm). The sum of C in these fractions (microaggregate protected C) was 468 ± 29, 696 ± 171, 673 ± 70 g C m−2 in the agricultural, afforested, and forested soils at Kemptville, respectively. The difference in the microaggregate protected C between the agricultural and the afforested soils accounted, on average, for 20% of the difference in whole SOC stocks between the soils. We conclude, SOC is stabilized for a relatively longer term within microaggregates formed in afforested and forest systems. Therefore, we suggest a new fractionation scheme to isolate this microaggregate associated SOC for assessing the impact of land use, land management, and climate change on C storage.
Keywords: CO2; organic C in soils; SOC